Pengaruh Komunikasi dan Budaya Organisasi Terhadap Kinerja Studi Kasus Pegawai Pengadilan Agama Indramayu - Ihya Sunnata Rosul; Arif Hartono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study was conducted to determine the effect of communication and organizational culture on employee performance through motivation as a mediating variable. This study is quantitative. The sample in this study amounted to 55 respondents based on purposive sampling technique. The study was conducted using a test tool in the form of SmartPLS 4.0. The results of the study indicate that communication and organizational culture have a positive and significant effect on employee performance through motivation as a mediating variable.